Green Supply Chain Management and SME’s, A Qualitative Study in Indonesian Marketplace - Antin Rakhmawati; Muhammad Nizar; Kusdi Rahardjo (Journal of International Conference Proceedings (JICP), 2019)
This study aims to explore the suitability and synchronization of business patterns that reduce environmental impact to creating green supply chains in general, and as extension of this exploration we aim at evaluating the current state of indonesian marketplace, especially in greengrocery marketplace of Malang city, the focus group method was selected to collect opinions of SMEs’s managers or owner, the focus group study was implemented in two sessions. We propose a conceptual model regarding interdependency within members of supply chain, in term of adopting environmentally aware attitude. It was found that SMEs in greengrocery marketplace in Malang city are still suffering and not doing well in critical aspects of GSCM such as SMEs members of the greengrocery market do not manage the waste maximally, the use information siystem for data sharing, standardization of business stalls on the marketplace and indecent competition, various recommendations were provided in this study, and we also propose solutions according to the problems were found.